Smart Multipurpose Lipstick / Izyan Khalidah Mohd Arif ... [et al.] - Mohd Arif, Izyan Khalidah; Abd Malek, Nur Nadhira; Roslan, Nur Amirah; Roslan, Najwa Nadeera (2019)
Smart Multipurpose Lipstick is a convenient lipstick that ate attached with USB flash drive and other additional technology such as camera and touchable menu screen. The idea of combining these features on a lipstick is due to the current lipstick that only available in one shade on a tube and cannot be refillable. Meanwhile, the size of USB flash drive is small and tend to lose easily. Ideas to generate this product was obtained from the internal idea sources and external idea sources. The internal idea sources were obtained through the observation and discussion among the team members. The external idea source was obtained via observations and face to face interview among female students in UITM Puncak Alam. The idea for the product features were screened, evaluated and filtered by reading from websites on the internet. The ideas were screened, evaluated and filtered by reading the materials from websites on the internet. They are divided into two parts which are the materials used and the design features. Instagram polling was used to in order perform market survey and concept testing for smart multipurpose lipstick. This survey was participated by random people who was on the timeline during 24 hours polling session. The respondents were asked with few closed ended questions about the product with its technology features added. In the market survey, from Instagram's polling, we are able to obtain the respondents average age, their opinion regarding the product features, expected price and conclude the most suitable population that suits with this product if it is being marketed. In the concept testing, from Instagram's polling, it helps us to enhance the current idea and identify the highest users in population after the product have been marketed. Majority of the respondents agree and give positive feedbacks regarding the smart multipurpose lipstick innovation. Test marketing for this product will be done according to 4P's concept which involve Product, Place, Price and Promotions. The shades of the lipstick will come in 3 different colours which are Rouge, Rose, Violet. The size of USB flash drive storage ranged from 32GB to 64GB. This product will be tested to be marketed in UITM Puncak Alam and we targeted female students as the respondents. The price of smart multipurpose lipstick is RM184.00. As for promotion purposes, we also create interesting flyers which contains advantages and information in details.